Experimental Study on the use of Pumice on the Rigid Pavement - Abdul Gaus; Imran Imran; Chairul Anwar; Liska Novianti (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
The Pumice sand is a bright colored butian type, containing foam made from glass-walled bubbles and usually referred to as silicate volcanic glass granules. This pumice sand can be used as a substitute for normal sand as fine aggregate in a mixture of concrete mix. Based on the characteristic test examination, it can be seen that in testing the characteristics of pumice sand to the specifications of normal sand in specific gravity testing and weight testing of quicksand obtained results that are smaller than the specifications of normal sand and absorption tests obtained results greater than specifications on normal sand. The results of the normal sand compressive strength at BN is 250.95 kg /cm2 while the results of the floating sand concrete compressive strength on BPA is 224, 965 kg /cm2. Based on the research it can be concluded that with the same quality of concrete, the quality of K-250 is different in comparison to the compressive strength of concrete in normal sand and pumice sand concrete shows almost the same results. Therefore, more in-depth research is needed regarding the use of pumice sand instead of normal sand in a mixture of concrete mix